2018
DOI: 10.3389/fmicb.2017.02695
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Heterogeneity in Sugar Utilization by E. coli Is Generated by Stochastic Dispersal of the General PTS Protein EI from Polar Clusters

Abstract: Although the list of proteins that localize to the bacterial cell poles is constantly growing, little is known about their temporal behavior. EI, a major protein of the phosphotransferase system (PTS) that regulates sugar uptake and metabolism in bacteria, was shown to form clusters at the Escherichia coli cell poles. We monitored the localization of EI clusters, as well as diffuse molecules, in space and time during the lifetime of E. coli cells. We show that EI distribution and cluster dynamics varies among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…Hence, the activity of EI inversely correlates with the level of TmaR in the cell. These results strengthen our previous results, which suggested that clustering of EI negatively correlates with EI activity (15).…”
Section: Tmar-mediated Ei Localization Affects Sugar Uptake By the Ptsupporting
confidence: 92%
See 4 more Smart Citations
“…Hence, the activity of EI inversely correlates with the level of TmaR in the cell. These results strengthen our previous results, which suggested that clustering of EI negatively correlates with EI activity (15).…”
Section: Tmar-mediated Ei Localization Affects Sugar Uptake By the Ptsupporting
confidence: 92%
“…Although EI-mCherry activity has been demonstrated previously (13) and shown to be comparable to that of wild-type EI (15), not only did we verify this again (see SI Appendix, Fig. S9), but we also asked if EI-mCherry fluorescent signal correlates with EI-mCherry level.…”
Section: Tmar and The General Pts Protein Ei Exhibit Co-localization mentioning
confidence: 65%
See 3 more Smart Citations